Green Approaches in Biotic Stress Management of Chilli Using Flourescent Pseudomonas - Naik, M. K.; Reshma, P.; Amaresh, Y. S.; Aswathanaraya, D. S.; Hosmani, A. (International Journal of Economic Plants, 2016)
The present field investigation was carried out to study the effect of green approaches in Biotic Stress Management of Chilli Using Flourescent Pseudomonas. It has been found that the present trend is to practice integrated pest management by integrating various bio inputs such as fluorescent Pseudomonas with, pesticides, plant products such as neem cake, Farm Yard Manure and several other inputs to mitigate diseases and pests.Among the various plant growth promoting rhizobacteria (PGPR), fluorescent Pseudomonas is considered to be the most important since they have both plant growth promotion activity as well as production of anti-pathogenic secondary metabolites. Many of them promote plant growth by suppressing pathogenic microorganisms, synthesizing growth stimulating plant hormones, promoting increased plant disease resistance.The modern agriculture is highly dependent on chemicals for plant disease management. It is neither possible to suddenly switch over to biological control nor biocontrol alone will be able to replace chemical control. Hence, the present study aims at identification of potential fluorescent Pseudomonas isolates with broad spectrum antibiotics, such as 2,4, DAPG, phenazine, pyoluterine and other antimicrobial compounds, hydrogen cyanide, salicylic acid, siderophore, and PR proteins etc. The investigation also describes the compatibility of PGPR with pesticides, formulation, shelf life and its delivery as an integral component in sustainable management of biotic stresses in chilli.